1990
DOI: 10.2307/3898920
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Riparian Vegetation Structure between Grazed Areas and Exclosures

Abstract: The valuable role that healthy riparian ecosystems play in regional diversity of plant and wildlife communities is just beginning to be recognized. Resource managers need to know how degraded riparian areas respond to changes in management, such as reduction and elimination of grazing. Differences in vegetation structure were examined in a montane riparian zone in northcentral Colorado after 30 years of cattle exclusion and continued, but reduced, grazing pressure. In order to assess the changes in the riparia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
2
4

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(118 citation statements)
references
References 6 publications
7
105
2
4
Order By: Relevance
“…These results contrast with findings that grazing had no effect on shoot frequency and density (Ratliff and Westfall 1987) or cover (Schulz and Leininger 1990) of Nebraska sedge. Our data indicate that Nebraska sedge may exhibit significant increases in aerial cover when released from grazing.…”
Section: Discussioncontrasting
confidence: 91%
“…These results contrast with findings that grazing had no effect on shoot frequency and density (Ratliff and Westfall 1987) or cover (Schulz and Leininger 1990) of Nebraska sedge. Our data indicate that Nebraska sedge may exhibit significant increases in aerial cover when released from grazing.…”
Section: Discussioncontrasting
confidence: 91%
“…Grazing reduced the height of standing dead materials in all sites except Estevan and Parkbeg. Litter cover and accumulation, measured by its thickness, were also reduced by grazing, similar to previous reports (Schulz and Leininger 1990). Clubmoss cover was site dependent, but grazing tended to increase the cover of dead clubmoss in at least 2 moderately grazed sites (GNP and Arena).…”
Section: Effect Of Grazing On Sward Structuresupporting
confidence: 89%
“…However, we expected that livestock grazing would affect the amount of live vegetation during the entire year, not just during the spring. Previous studies consistently found more litter inside exclosures, which would correspond to a lower proportion of live vegetation [41][42][43]. The proportion of live vegetation mass did not differ between 1994-95 and 2005-06.…”
Section: Mass Of Live Vegetationmentioning
confidence: 60%